Reductive Precipitation of Gold by Dissimilatory Fe(III)-Reducing Bacteria and Archaea - Kashefi, Kazem (American Society for Microbiology, 2001)
Studies with a diversity of hyperthermophilic and mesophilic dissimilatory Fe(III)-reducing Bacteria and Archaea demonstrated that some of these organisms are capable of precipitating gold by reducing Au(III) to Au(0) with hydrogen as the electron donor. These studies suggest that models for the formation of gold deposits in both hydrothermal and cooler environments should consider the possibility that dissimilatory metal-reducing microorganisms can reductively precipitate gold from solution.